PROFIL MODAL SOSIAL DAN TINGKAT PARTISIPASI PETERNAKPADA PENGEMBANGAN SAPI POTONG DI KABUPATEN TEBO PROPINSI JAMBI - Syafril Hadi (Universitas Muhammadiyah Sidoarjo, 2014)
The purposes of this research are to describethe level of social capital and to identify the level ofparticipation of cattle breedersin Tebo district. The method used in this research is descriptive analysis by usingquantitative approach. Thesample collection technique used in this research is purposive random sampling whichconsistsof five people as a unit of analysis. The questionnaires weregiven to 165 respondences who breed the cattlein Tebo.The results of this research show that the level of social capital of cattle breeders in Tebo district is in the very high category and the participant level of cattle breeders is also in the high category.